2018
DOI: 10.1103/physrevd.97.114504
|View full text |Cite
|
Sign up to set email alerts
|

Finite-density transition line for QCD with 695 MeV dynamical fermions

Abstract: We apply the relative weights method to SU(3) gauge theory with staggered fermions of mass 695 MeV at a set of temperatures in the range 151 ≤ T ≤ 267 MeV, to obtain an effective Polyakov line action at each temperature. We then apply a mean field method to search for phase transitions in the effective theory at finite densities. The result is a transition line in the plane of temperature and chemical potential, with an end point at high temperature, as expected, but also a second end point at a lower temperat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The main source of interest is the possibility of obtaining information about QCD at finite baryon density via analytic continuation, thus partially avoiding the sign problem. Moreover, numerical results at imaginary µ are also a relevant test bed for effective models trying to reproduce the properties of QCD at finite density [27][28][29]. Furthermore, imaginary chemical potentials are an interesting extension of the QCD phase diagram per se, as, for particular choices of the chemical potentials, one recovers exact symmetries even in the presence of finite quark masses, leading to the presence of interesting phase transitions and critical points which, in principle, could be relevant also for the physical region of the phase diagram.…”
Section: Introductionmentioning
confidence: 99%
“…The main source of interest is the possibility of obtaining information about QCD at finite baryon density via analytic continuation, thus partially avoiding the sign problem. Moreover, numerical results at imaginary µ are also a relevant test bed for effective models trying to reproduce the properties of QCD at finite density [27][28][29]. Furthermore, imaginary chemical potentials are an interesting extension of the QCD phase diagram per se, as, for particular choices of the chemical potentials, one recovers exact symmetries even in the presence of finite quark masses, leading to the presence of interesting phase transitions and critical points which, in principle, could be relevant also for the physical region of the phase diagram.…”
Section: Introductionmentioning
confidence: 99%
“…This was studied in the strong coupling expansion [28], but also in full lattice QCD simulations. It was found that this effective theory is more tractable than the underlying lattice gauge theory (LGT) when confronting the sign problem at finite density, for recent advances see [29]. The developed algorithms in this article can be adapted to this problem, where the individual Polyakov lines and not their average over the whole lattice are constrained.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies employed renormalizationgroup inspired bond moving procedures [82] and microcanonical methods [83]. More recent efforts have been the inverse Monte Carlo method [84,85], the relative weights method [86][87][88][89][90][91] and the expectation value matching procedure in [92].…”
Section: Derivation Of the Effective Actionsmentioning
confidence: 99%